Supply Chain Analysis of Village Chicken Business Provider of Meat in Central Lombok District - Blegoh Julianto, Totok; Hermasyah; Bulkaini; Multazam, Syamsul (Journal of Islamic Economics Perspectives, 2024)
This research aims to analyze the supply chain of free-range chicken businesses providing meat in Central Lombok Regency. The number of respondents in the research was 54 people who were obtained randomly purposive sampling And snowball sampling with survey methods. Efficient free-range chicken distribution channels/supply chains. The data obtained was analyzed using the Marketing Margin Analysis method. The research results show that The efficient marketing channels for free-range chickens providing meat in Central Lombok Regency are Breeders ? Chicken and Carcass Collectors ? Restaurants ? Final Consumers and the income margin for each business actor marketing free-range chicken providing meat in Central Lombok Regency, namely farmers get a profit of IDR 4,600/ live chickens, live chicken collectors get a profit of Rp. and restaurants for as much as IDR 33,000/portion of ready-to-eat free-range chicken.